Capitalizing on the Demographic Transition : Tackling Noncommunicable Diseases in South Asia - Engelgau, Michael Maurice (World Bank, 2012)
This book looks primarily at Cardio Vascular Disease (CVD) and tobacco use because they account for a disproportionate amount of the Non Communicable Disease (NCD) burden the focus is strategic rather than comprehensive. It considers both country and regional level approaches for tackling NCDs, as many of the issues and challenges of mounting an effective response are common to most South Asian countries. The prevention and control of NCDs constitute a development issue that low-income countries in South Asia are already facing. Both country and regional-level strategies are important because many of the issues and challenges of mounting an effective response to NCDs are common to most South Asian countries, even though their disease burden profiles vary. Hence, the rationale for this book is that strategic decisions for prevention and treatment of NCDs can effectively address the future burden of disease, promote healthy aging, and increase the potential benefit from the demographic transition, thus contributing to economic development. This book's goal is to encourage countries to develop, adopt, and implement effective and timely country and regional responses that reduce the population-level risk factors and NCD disease burden.